The Relationship Between Preschool Inclusive Education Teachers’ Organizational Support and Work Engagement: The Mediating Role of Teacher Self-Efficacy - Jiao, Chunlan; Qian, Jing; Liu, Huan (Frontiers in Psychology, 2022)
This study aims to explore the relationship and mechanism between the preschool inclusive education teachers‘ organizational support, teacher self-efficacy and work engagement. This study adopted the organizational support scale, inclusive education efficacy scale and work engagement scale, measured for 600 preschool inclusive education teachers, eventually obtained 568 effective questionnaires, establish research model, and analyzed the data by the structural equation model (SEM). There are significantly more female (65.1%) than male (34.9), and the majority (57.6%) were public kindergarten. Organizational support significant positively affects teachers’ self-efficacy ( = 0.526, p<0.001) and work engagement ( = 0.385, p<0.001) in preschool inclusive education. Preschool teachers’ self-efficacy has a significant positive impact on work engagement ( = 0.222, p<0.001). Preschool teachers’ self-efficacy plays a partial mediating role between organizational support and work engagement ( = 0.202, p<0.001, CIs = [0.077, 0.305]). Organizational support not only directly affects teachers’ self-efficacy and work engagement in preschool inclusive education, but also indirectly affects their work engagement through preschool teachers’ self-efficacy, which provides theoretical and practical guidance for the research of inclusive education.